Primary Merkel cell carcinoma of the salivary gland: a clinicopathologic study of four cases with a review of literature - Gyuheon Choi; Joon Seon Song; Hee Jin Lee; Gi Hwan Kim; Young Ho Jung; Yoon Se Lee; Kyung-Ja Cho (Journal of Pathology and Translational Medicine)
Background Primary Merkel cell carcinoma of the salivary gland is currently not listed in the World Health Organization classification. However, cases of Merkel cell type neuroendocrine carcinomas of the salivary gland with perinuclear cytokeratin 20 positivity have been intermittently reported. We here investigated the clinicopathologic features of additional cases. Methods Data of four cases of Merkel cell type small cell neuroendocrine carcinoma of the salivary gland were retrieved. To confirm the tumors’ primary nature, clinical records and pathologic materials were reviewed. Optimal immunohistochemical staining was performed to support the diagnosis. Results All tumors were located in the parotid gland. Possibilities of metastasis were excluded in all cases through a meticulous clinicopathological review. Tumor histology was consistent with the diagnosis of small cell neuroendocrine carcinoma. Tumors’ immunohistochemical phenotypes were consistent with Merkel cell carcinoma, including Merkel cell polyomavirus large T antigen positivity in two of the four cases. Conclusions Merkel cell carcinomas can originate in salivary glands and are partly associated with Merkel cell polyomavirus infection as in cutaneous Merkel cell carcinomas.